2021
DOI: 10.1101/2021.10.25.465693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-cancer in silico analysis of somatic mutations in G-protein coupled receptors: The effect of evolutionary conservation and natural variance

Abstract: G protein-coupled receptors (GPCRs) form the most frequently exploited drug target family, moreover they are often found mutated in cancer. Here we used an aggregated dataset of mutations found in cancer patient samples derived from the Genomic Data Commons and compared it to the natural human variance as exemplified by data from the 1000 Genomes project. While the location of these mutations across the protein domains did not differ significantly in the two datasets, a mutation enrichment was observed in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Therefore, it is not surprising that P302L 7.50 and P302R 7.50 mutants showed a loss of receptor activation, as the receptor is no longer able to complete this movement. Noteworthy is that mutations in highly conserved positions of TM regions, including 6.50 and 7.50, rank among the most frequent in the GDC and 1000 genomes datasets, as shown recently by Bongers et al [36].…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, it is not surprising that P302L 7.50 and P302R 7.50 mutants showed a loss of receptor activation, as the receptor is no longer able to complete this movement. Noteworthy is that mutations in highly conserved positions of TM regions, including 6.50 and 7.50, rank among the most frequent in the GDC and 1000 genomes datasets, as shown recently by Bongers et al [36].…”
Section: Discussionmentioning
confidence: 63%
“…From the Genomic Data Commons database (version 22.0; as collected by Bongers et al) [ 22 , 23 ], a total of 58 A 2A AR single-site missense mutations were identified in patients of different cancer types. As shown in Figure 1 , these mutations were distributed all over the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these 15 mutations were selected for further investigation. Of note, A265T ECL3 and S281L 7.46 have also been identified as natural variants (The 1000 Genomes Project Consortium, as collected by Bongers et al) [ 23 , 25 ], while the other mutations could be considered cancer specific ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous structural studies and crystal structures of hA 1 AR provided us with information on crucial residues for ligand binding and receptor activation, as well as essential interactions in the inactive receptor state and G protein coupling [17,[23][24][25]. Moreover, compared to other residues, accumulation of cancer-related mutations has been observed in highly conserved residues of the TM domains [26]. Therefore, in this study, we studied 13 single-site point mutations located at the 7-TM domains of A 1 AR obtained from The Cancer Genome Atlas (TCGA).…”
Section: Discussionmentioning
confidence: 99%